Therapeutic Protein–Polymer Conjugates: Advancing Beyond PEGylation - Pelegri-O’Day, Emma M; Lin, En-Wei; Maynard, Heather D (Journal of the American Chemical Society, 2014)
Protein–polymer conjugates are widely used as therapeutics. All Food and Drug Administration (FDA)-approved protein conjugates are covalently linked to poly(ethylene glycol) (PEG). These PEGylated drugs have longer half-lives in the bloodstream, leading to less frequent dosing, which is a significant advantage for patients. However, there are some potential drawbacks to PEG that are driving the development of alternatives. Polymers that display enhanced pharmacokinetic properties along with additional advantages such as improved stability or degradability will be important to advance the field of protein therapeutics. This perspective presents a summary of protein–PEG conjugates for therapeutic use and alternative technologies in various stages of development as well as suggestions for future directions. Established methods of producing protein–PEG conjugates and new approaches utilizing controlled radical polymerization are also covered.